PEMBENTUKAN KARAKTER ANAK SD/MI MELALUI PENDIDIKAN PRAMUKA - Muhammad MUhammad (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Boy Scouts are able to realize the personal character of a learner, especially at the basic level in elementary school. It can be established the nature of discipline for learners in daily activity. The purpose of scouting is to educate and develop the nurture of children and youth in the mental, moral, spiritual, intellectual youth to become good and useful individual, society, religion and nation. Character education aims to improve the quality of the implementation and results of school education towards achieving the formation of character and noble character of learners as a whole, integrated and balanced. Through education scouts expected that learners are able to independently improve science, study, internalize and personalize the character values and noble character that manifested itself in the behavior of everyday life. Education scouts created the character of learners who complete and thorough investigation not only shaping students into a personal smart and good, but also mold them into good actors for change in his own life, which in turn will donate a change in the social order of society.